1988
DOI: 10.1159/000281341
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes in Penile Vessels during Erection: The Mechanism of Obstruction of Arteries and Veins at the Tunica albuginea in Dog Corpora cavernosa

Abstract: The present study deals with morphological changes during erection both in the penile deep artery supplying the corpus cavernosum and in veins draining it. These vessels were shown to maintain wide lumina in the flaccid state. In the erect state induced by injection of papaverine, the postcavernous venules were compressed between the cavernous sinuses and the tunica albuginea. Simultaneously, the penile deep artery and the penetrating vein were strangulated by stretched collagen bundles in the inner layer of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…penile erection have greatly improved our understanding of erectile process and the associated pathophysiology of erectile dysfunction. It is clear now that the key events in the erection process are the relaxation of the penile arterial system, which enhances blood pressure to the corpora cavernosa, and the relaxation of trabecular smooth muscle, which allows the expansion of lacunars' spaces and the reduction of cavernosal veinous outflow by the compression of the veinules against the tunica albuginea (Lue et al, 1983;Anderson and Wagner, 1995;Hanyu, 1998;El-Sakka and Lue, 2004). These processes are generally accepted to be under neuroregulatory control and involve adrenergic, cholinergic, non-adrenergic and non-cholinergic neuroeffector systems.…”
Section: Introductionmentioning
confidence: 99%
“…penile erection have greatly improved our understanding of erectile process and the associated pathophysiology of erectile dysfunction. It is clear now that the key events in the erection process are the relaxation of the penile arterial system, which enhances blood pressure to the corpora cavernosa, and the relaxation of trabecular smooth muscle, which allows the expansion of lacunars' spaces and the reduction of cavernosal veinous outflow by the compression of the veinules against the tunica albuginea (Lue et al, 1983;Anderson and Wagner, 1995;Hanyu, 1998;El-Sakka and Lue, 2004). These processes are generally accepted to be under neuroregulatory control and involve adrenergic, cholinergic, non-adrenergic and non-cholinergic neuroeffector systems.…”
Section: Introductionmentioning
confidence: 99%
“…Beckett et al [11] using antegrade serial angiography suggested that the internal pudendal artery or the penile deep artery might be mechanically occluded in rigid erection. Hanyu [12] believed that the deep artery was compressed by the tunica albuginea in the rigid phase. However, these stud ies lacked evidence to account for the actual prevention of the arterial backflow from the corpus cavernosum under high pressure, from the viewpoint of a retrograde pres sure-flow study.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [8], we proposed a mechanism of venous obstruction during erection of the dog CCP. namely that relaxation of arterial and trabecular smooth muscles facilitates the CCP to expand and the albuginea to stretch.…”
Section: Discussionmentioning
confidence: 99%
“…Dripping with a con stant and slow' rate was observed even in the rigid state. Since the penile deep artery has been observed to be perfectly occluded in the tunica albuginea in the rigid state [5,8], the value o f FA during the rigid state (FA(rigjli)) was estimated to be equal to a flow out of the CCP via minute lateral branches o f the penile deep artery. Therefore, the inflow rate into the CCP (Fa) was estimated as follows: Fa = FAFa (rigid)-When the CCP w'as in such a stable state as the cavernous pressure (Prav) was steady, the venous outflow rate (Fv) was regarded to be equal to the Fa.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation